Incorporating Longitudinal Comorbidity and Acute Physiology Data in Template Matching for Assessing Hospital Quality: An Exploratory Study in an Integrated Health Care Delivery System. Issue 5 (May 2018) - Hu, Wenqi; Chan, Carri W.; Zubizarreta, José R.; Escobar, Gabriel J.
Abstract : Objective: We sought to build on the template-matching methodology by incorporating longitudinal comorbidities and acute physiology to audit hospital quality. Study Setting: Patients admitted for sepsis and pneumonia, congestive heart failure, hip fracture, and cancer between January 2010 and November 2011 at 18 Kaiser Permanente Northern California hospitals. Study Design: We generated a representative template of 250 patients in 4 diagnosis groups. We then matched between 1 and 5 patients at each hospital to this template using varying levels of patient information. Data Collection: Data were collected retrospectively from inpatient and outpatient electronic records. Principal Findings: Matching on both present-on-admission comorbidity history and physiological data significantly reduced the variation across hospitals in patient severity of illness levels compared with matching on administrative data only. After adjustment for longitudinal comorbidity and acute physiology, hospital rankings on 30-day mortality and estimates of length of stay were statistically different from rankings based on administrative data. Conclusions: Template matching–based approaches to hospital quality assessment can be enhanced using more granular electronic medical record data. Abstract : Supplemental Digital Content is available in the text.